MY SAY: Whither the Hippocratic oath? - Abd Razak, Dzulkifli (2011)
The news that the government is imposing a five-year moratorium on medical programmes for a variety of reasons cannot be more timely. Malaysia is fast becoming a doctor-exporting country and one could argue that such drastic action should have been taken much earlier. By now the diagnosis seems to be much more dire. A former minister of health says Malaysia will be producing about 4,500 doctors a year come January 2011. And at this rate of growth, the number of doctors will double from the current 30,000 to 55,000 or 60,000 five or six years from now.